Nucleotide sequences of trpA of Salmonella typhimurium and Escherichia coli: an evolutionary comparison. - Nichols, B P (1979)
The complete nucleotide sequences of trpA of Salmonella typhimurium and Escherichia coli were determined. The nucleotide sequences are 24.8% divergent, compared with amino acid sequence divergence of 14.9%. Over half of the codons of each gene contain synonymous nucleotide changes. The pattern of synonymous nucleotide changes is consistent with the interpretation that such changes result from random mutational events. We do not find any evidence indicating that codon selection or RNA structure is of major selective value. We conclude that polypeptide function is the primary basis of selection in trpA and that most synonymous codon changes are selectively neutral.